Gut Microbiota Modulates Intestinal Pathological Injury in Schistosoma japonicum-Infected Mice - Zhang, Beibei; Wu, Xiaoying; Song, Qiuyue; Ning, An; Liang, Jinyi; Song, Langui; Liu, Jiahua; Zhang, Yishu; Yuan, Dongjuan; Sun, Xi; Wu, Zhongdao (Frontiers in Medicine, 2020)
Trapping of Schistosoma japonicum (S. japonicum) eggs in host tissue, mainly in the intestine and liver, causes severe gastrointestinal and hepatic granulomatous immune responses and irreversible fibrosis. Although the gut microbiota plays a central role in regulating pathological responses in several diseases, the effect of the gut microbiota on the pathologenesis progression of schistosomiasis remains largely unknown. In this study, we aimed to investigate the regulatory function of the gut microbiota in schistosomiasis japonica. We found that the depletion of the gut microbiota significantly ameliorated egg granulomas formation and fibrosis in the intestine of infected mice. This role of the gut microbiota in intestinal granuloma formation and fibrosis was reinforced when normal and infected mice were housed together in one cage. Notably, changes in the gut microbiota induced by S. japonicum infection were partly reversible with microbiota transfer in the cohousing experiment. Transfer of the gut microbiota from normal to infected mice attenuated the intestinal pathological responses. Depletion of the gut microbiota by antibiotics, or transfer of the gut microbiota from normal to infected mice decreased the levels of IL-4, IL-5 and IL-13 and promoted the production of cytokines IL-10 and TGF-β in infected mice. Our findings indicated a regulatory effect of the gut microbiota on intestinal pathological injury associated with schistosomiasis japonica in mice, and thus suggested a potential strategy for schistosomiasis treatment.